Analisis Komparatif Gaya Komunikasi Pemimpin Organisasi Kemahasiswaan Legislatif Berdasarkan Gender - Atika, Salma; Julianto, Edi Nurwahyu (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study examines the differences in leadership communication styles among gender-based organizations. One of the issues raised is gender stereotypes in leadership, where men are often considered more competent than women. The purpose of this study was to see how to the communication styles of male and female leaders in legislative student organizations at Semarang City University. The method used was a qualitative descriptive approach, with research subject consisting of four informants, namely two male leaders and two female leaders in various student organizations at Semarang City University. The findings show that male and female leaders can demonstrate effective communication styles in different situations, although there are differences in communication approaches. While male leaders tend to be more assertive and results oriented, female leaders tend to be more empathetic and communicative. The conclusion of this study is that a leaders’s communication style is influenced by gender, character, and organizational experience. All of these factors have an impact on how effectively a leader achieves organizational goals.